The Abdau Tradition as a Living Hadith: Interplay of Islamic Law and Local Customs in Qurban Ritual at Tulehu, Maluku - Rajab, Rajab; Ode, Wa Ulfa; Achyar, Gamal; M.Yunus, Fakhrurrazi (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Abdau represents a tradition of slaughtering Qurban practiced by the Muslim community of Tulehu during Eid al-Adha. This tradition commences with the meticulous preparation of three goats, which are bathed, dressed, and perfumed. They are then paraded through the village to the mosque for slaughter, accompanied by the chanting of salawat, dhikr, poems, and the pursuit of the tauhid flag along the route. This parade also showcases various cultural attractions, transforming it into a carnival that draws numerous tourists. Currently, Abdau faces significant criticism for allegedly breaching numerous fundamental principles of sharia. This research seeks to reveal the origins of this celebration and elucidate its connection to the practices derived from the Prophet's hadiths that persist within the community. This is a qualitative study, utilizing data gathered from written sources pertaining to the Abdau celebration, complemented by interviews with religious leaders, traditional authorities, and government officials in the Tulehu region who possess a deep understanding of the intricacies of the Abdau celebration. The data were subsequently examined utilizing the living hadith methodology. This study reveals that Abdau is an Islamic teaching rooted in the societal tradition, rather than a practice of a society that has undergone Islamization. The celebration of Abdau did not exist prior to the arrival of Islam; instead, it emerged concurrently with the establishment of the Tulehu region, which is home to a Muslim community. Examining the living hadith, the Abdau tradition in each of its ritual series reveals connections to the hadiths of the Prophet and its relevance to the Islamic law. Abdau is a tradition that involves the living hadith in Tulehu, particularly in the context of Qurban and its relation to the Islamic law.